The crises of multiculturalism : racism in a neoliberal age - Lentin, Alana; Titley, Gavan (London ; New York : Zed Books, 2011)
"Across the West, something called multiculturalism is in crisis. Re garded as the failed experiment of liberal elites, commentators and pol iticians compete to denounce its corrosive legacies; parallel communiti es threatening social cohesion, enemies within cultivated by irresponsi ble cultural relativism, mediaeval practices subverting national 'ways of life' and universal values. This important new book challenges this familiar narrative of the rise and fall of multiculturalism by challeng ing the existence of a coherent era of 'multiculturalism' in the first place. The authors argue that what we are witnessing is not so much a r ejection of multiculturalism as a projection of neoliberal anxieties on to the social realities of lived multiculture. Nested in an established post-racial consensus, new forms of racism draw powerfully on liberali sm and questions of 'values', and unsettle received ideas about racism and the 'far right' in Europe. In combining theory with a reading of re cent controversies concerning headscarves, cartoons, minarets and burka s, Lentin and Titley trace a transnational crisis that travels and is m ade to travel, and where rejecting multiculturalism is central to laund ering increasingly acceptable forms of racism." --Publisher's website.
Recited truths: the contours of multicultural crisis -- Let's talk a bout your culture: post-race, post-racism -- Free like me: the polyphon y of liberal post-racialism -- Mediating the crisis: circuits of belief -- Good and bad diversity: the shape of neoliberal racisms -- On one m ore condition: the politics of integration today.
Includes bibliographical references (p. [227]-273) and index.
Keywords: Multiculturalism; Racism; Neoliberalism